Attenuated Readiness Potential in the Absence of Executive Dysfunction in Adults With ADHD. (February 2017) - Seo, Bo-Kyung; Sartory, Gudrun; Kis, Bernhard; Scherbaum, Norbert; Müller, Bernhard W.
Objective: Patients with ADHD display a decreased contingent negative variation in Go/NoGo tasks. It is unclear whether the attenuation is due to deficits of executive function or to disorder of motor planning. The readiness potential (RP) recorded during self-initiated movements could cast light on this question.Method: RP was recorded in 25 stably medicated adult ADHD patients and 21 healthy controls matched for age, education, and verbal IQ. Participants also completed neuropsychological tests of executive function.Results: Compared with healthy controls, ADHD patients showed significantly diminished RP peaks and also decreased negativity in preparation of the movement at frontal locations. There were no significant group differences with regard to tests of executive function.Conclusion: In adults with ADHD, deficits of motor organization are also manifest in situations not involving external stimulus processing. The attenuated RP occurred in the absence of executive dysfunction. Results are consistent with partial independence between motor and executive dysfunction in ADHD.